Selenium-enriched yeast modulates the metal bioaccumulation, oxidant status, and inflammation in copper-stressed broiler chickens - Habotta, Ola A.; Wang, Xiaoyan; Othman, Hamzah; Aljali, Abdulrahman A.; Gewaily, Mahmoud; Dawood, Mahmoud; Khafaga, Asmaa; Zaineldin, Amr I.; Singla, Rajeev K.; Shen, Bairong; Ghamry, Heba I.; Elhussieny, Eman; et al. (Frontiers in Pharmacology, 2022)
Copper (Cu) could be seriously hazardous when present at excessive levels, despite its vital contribution to various cellular processes. Selenium-enriched yeast (SeY) was reported to improve the health and metabolic status in broiler chicken. Hence, our study was endeavoured to illustrate the mitigating efficacy of SeY on Cu-induced hepatic and renal damage. Cobb chicks aged one day were allocated into four experimental groups and offered a basal diet, SeY (0.5 mg/kg), CuSO4 (300 mg/kg), or SeY plus CuSO4 in their diets for 42 days. Our results revealed that SeY supplement antagonized significantly the Cu accumulation in livers and kidneys of exposed birds. Marked declines were also detected in the AST, ALT, urea, and creatinine levels, besides marked increases in total protein, glycerides, and cholesterol in the SeY-supplemented group. Moreover, enhancement of cellular antioxidant biomarkers (SOD, CAT, GPx, and GSH) along with lowered MDA contents were achieved by SeY in hepatic and renal tissues. Further, SeY exerted a noteworthy anti-inflammatory action as indicated by decreased inflammatory biomarkers (IL-1β and TNF-α) and NO levels in both organs. Noticeable histopathological alterations of both organs further validated the changes in the markers mentioned above. To sum up, our findings that SeY can be considered a potential feed supplement for alleviating Cu-induced hepatic and renal damage in broilers, possibly via activation of antioxidant molecules and lessening the inflammatory stress.